The Relationship between Electricity Consumption, Oil Prices, and Economic Growth in Indonesia - Prastowo Prastowo; Laillil Putri Damayanti (Universitas Ahmad Dahlan, Yogyakarta, 2022)
This study aims to analyze the relationship between electricity consumption, oil prices and economic growth. The data used are from 1971 to 2014 using a case study of the country of Indonesia. This research model uses the Vector Error Correction Model (VECM) regression. The results show that there is a long-term balance in electricity consumption, oil prices and economic growth. However, there is no short-term relationship on electricity consumption, oil prices and economic growth. Therefore, it is recommended that the government maximize the investment sector in industrialization so that the level of electricity consumption in terms of industry increases and can increase economic growth. In addition, this policy can create job opportunities so that residents can have greater job opportunities.